TREAT-AND-EXTEND REGIMENS WITH ANTI-VEGF AGENTS IN RETINAL DISEASES: A Literature Review and Consensus Recommendations. Issue 8 (August 2015) - Freund, K. Bailey; Korobelnik, Jean-François; Devenyi, Robert; Framme, Carsten; Galic, John; Herbert, Edward; Hoerauf, Hans; Lanzetta, Paolo; Michels, Stephan; Mitchell, Paul; Monés, Jordi; Regillo, Carl; et al.
Abstract : Purpose: A review of treat-and-extend regimens (TERs) with intravitreal anti–vascular endothelial growth factor agents in retinal diseases. Methods: There is a lack of consensus on the definition and optimal application of TER in clinical practice. This article describes the supporting evidence and subsequent development of a generic algorithm for TER dosing with anti–vascular endothelial growth factor agents, considering factors such as criteria for extension. Results: A TER algorithm was developed; TER is defined as an individualized proactive dosing regimen usually initiated by monthly injections until a maximal clinical response is observed (frequently determined by optical coherence tomography), followed by increasing intervals between injections (and evaluations) depending on disease activity. The TER regimen has emerged as an effective approach to tailoring the dosing regimen and for reducing treatment burden (visits and injections) compared with fixed monthly dosing or monthly visits with optical coherence tomography–guided regimens (as-needed or pro re nata). It is also considered a suitable approach in many retinal diseases managed with intravitreal anti–vascular endothelial growth factor therapy, given that all eyes differ in the need for repeat injections. Conclusion: It is hoped that this practical review and TER algorithm will be of benefit to health care professionals interested in the management of retinal diseases. Abstract : Supplemental Digital Content is Available in the Text.There is a lack of consensus on the definition and optimal application of treat-and-extend regimens (TERs) in clinical practice. This article describes the supporting evidence and subsequent development of a generic algorithm for TER dosing with anti–vascular endothelial growth factor agents, considering factors such as criteria for extension.